Vaccines - Plotkin, Stanley A; Mortimer, Edward E (W.B. Saunders, 1994)
As the debate over health care reform continues, this reference covers everything about vaccines in current, public use - the diseases being guarded against, their epidemiology, the composition of the vaccines, their immunogenicity, side effects, and the impact on public health. It gives both the theoretical and practical information needed to use the vaccines most effectively. Features new to this edition include: new chapters on Japanese B. encephalitis, tick-borne encephalitis, and anthrax; extensive revisions made to chapters on mumps, hepatitis B, BCG, HIV, and public health considerations; new authors who have contributed to discussions on the adenovirus vaccine, meningococcal vaccines, and cytomegalovirus vaccines; coverage of recent advances - including vaccines not yet licensed, alerting readers to new developments in inoculating against hepatitis A, varicella and AIDS; and a practical approach, looking at non-clinical considerations of effective vaccination, such as legal issues and the impact of vaccines on public health.
Keywords: epidemiologie; Vaccines; mikrobiologie, lékařská mikrobiologie; Vaccination; vakcíny; vakcinace